Scenario's for Revolution in Sid Meier's Civilization (1991) and Sid Meier's Colonization (1994) - van der Burg, Martijn (Locus–Tijdschrift voor Cultuurwetenschappen, 2023)
This article examines the function and representation of the historical concept of ‘revolution’ in Sid Meier’s Civilization and its offshoot Colonization. Revolution is a central concept in both games, although it has a different character and purpose in each. Both offer their own take on revolutions in history, in terms of origins, trajectories and consequences. Revolution has a central place in the gameplay, but their operationalization of the concept differs from each other. Differences stem partly from history’s place in the video games.